Aging and Environmental Enrichment Exacerbate Inflammatory Response on Antibody-Enhanced Dengue Disease in Immunocompetent Murine Model. (September 2013) - Diniz, D.G.; Foro, C.A.R.; Sosthenes, M.C.K.; Demachki, S.; Gomes, G.F.; Malerba, G.A.; Naves, T.B.; Cavalcante, E.A.D.; Sousa, A.M.C.; Ferreira, F.A.B.; Anjos, P.C.S.; Neto, A.L.C.; et al.
We previously demonstrated in young mice that in comparison with animals raised in an impoverished environment (IE), animals from an enriched environment (EE) show more severe dengue disease, associated with an increased expansion of memory T target cells. Because active older adults show less functional decline in T-cell adaptive immunity, we hypothesized that aged mice from EE would show higher mortality and T-lymphocyte expansion than mice from IE. To test this hypothesis, we administered serial i.p. injections of anti-DENV2 hyperimmune serum, followed 24 h later by DENV3 (genotype III)-infected brain homogenate. Control mice received equal volumes of serum but received uninfected brain homogenate. The presence of virus or viral antigens was indirectly detected by real-time quantitative RT-PCR and immunohistochemistry. Compared to infected IE animals, EE mice, independent of age, showed higher mortality and more intense clinical signs. Compared to young mice, the higher mortality of aged mice was associated with a higher degree of T lymphocytic hyperplasia in the spleen and infiltration in kidneys, liver, and lungs, but less viral antigen immunolabeling. We propose that a higher expansion of T cells and serotype cross-reactive antibodies are associated with disease severity in aged mice.